Answer:
x=1
Step-by-step explanation:
So, first you make sure to multiply the parenthesis by the negative so then it would be,
-x-3=2x-6
Then you add the -3 from the right to the other side
so, -x=2x-3
Then you want all the X variables to one side so you subtract the 2x to both sides.
so, -3x=-3
divide both by -3
x=1
Answer:2.75
Step-by-step explanation:
Answer:
The solutions are the following:
- z=2(cos(π6)+isin(π6))=√3+12i
- z=2(cos(2π3)+isin(2π3))=−1+i√3
- z=2(cos(7π6)+isin(7π6))=−√3−12i
- z=2(cos(5π3)+isin(5π3))=1−i√3
<em>hope this helps!! :) --Siveth</em>
It does not. So Long as the length is multipled by the height aka Long edge multiplied with the short edge, you will obtain the area of the rectangle.